Topological Modelling of Grammatical and Lexical Aspect in English - Skrzypczak, Waldemar (Research in Language, 2007)
This paper stems from a broader research project entitled Analog-based Modelling of Meaning Representations in English (Skrzypczak 2006), and aims to present grammatical aspect and lexical aspect as two modes of encoding the temporal profiles within the conceptualisation of processes (terminologically, in Langackerian sense, imperfective and perfective processes, otherwise, variously labelled as stative and dynamic verbs, i. e. states vs. discrete ‘unitary’ events and nondiscrete ‘unbounded’ processes). It is assumed that aspect in both cases – as a process-profiling category – is analogous to the profiling of things and atemporal relations (in the sense of Langacker 1987, 1990, 2000), given the maximisation of the temporal domain in the characterisation of processes (perfective and imperfective, hence: dynamic and stative), and minimalisation of the temporal domain during the conceptualisation of things (conceptually independent entities) and atemporal relations (conceptually dependent atemporal configurations). The analogy between nouns and verbs in terms of ‘granularity’ has been so far variously addressed by Langacker (1990), Jackendoff (1991) and Talmy (2001), and also constitutes the core assumption in my research on topological modelling.